REFORMULATION OF REGULATIONS ON STRUCTURED, SYSTEMATIC, AND MASSIVE CRIMES IN ELECTION DISPUTE RESOLUTION - Fakhry Amin (Jurnal Ilmiah Advokasi, 2024)
Election result disputes often lead to structured, systematic, and massive (TSM) crimes that harm democracy and the nation. The regulations concerning TSM crimes in the Election Law are considered weak, necessitating reformulation to more effectively prevent and eradicate such practices. This research aims to identify the weaknesses in the regulation of TSM crimes in election result disputes and to formulate appropriate regulations to combat these practices. The study employs a normative legal method with statutory and conceptual approaches to examine the regulation of TSM crimes in election result disputes. The legal materials consist of legislation and academic literature, analyzed qualitatively normatively. The research findings indicate that the main weaknesses in the current TSM regulations are the unclear definitions and the insufficient criminal sanctions that fail to deter. The proposed reformulation includes providing an operational definition of TSM, increasing minimum sanctions, expanding the subjects of criminal acts to include corporations, regulating the concurrence of articles, expanding the authority of investigators, and enhancing inter-institutional cooperation. With these reforms, it is expected that TSM practices in elections can be more effectively prevented and eradicated. Keywords: Structured, Systematic, Massive, Election, Crime, Sanctions, Regulation.